Combination of Radiofrequency Ablation With Resiquimod to Treat Hepatocellular Carcinoma Via Inflammation of Tumor Immune Microenvironment and Suppression of Angiogenesis - Tian, Zhou; Hong, Baojian; Chen, Jianzhong; Tang, Zhe (Frontiers in Oncology, 2022)
Background Radiofrequency ablation (RFA) destroys tumors through hyperthermic injury, which induces the release of immunogenic intracellular substrates and damages associated molecular patterns (DAMPs) to evoke a systemic immune response, but its therapeutic effect is limited. This study aimed to combine RFA with an immunomodulator, resiquimod (R848), to enhance the RFA-induced antitumor immunity. Methods We performed RFA on subcutaneous tumors in immunocompetent mice and intraperitoneally injected R848 to observe the efficacy of the combination therapy. Our research investigated changes in the composition of tumor-infiltrating immune cells in primary and distant tumors by flow cytometry. Natural killer (NK) cell depletion experiment was applied to confirm the role of NK cell in the combination therapy. The expression levels of cytokines and chemokines were detected by real-time quantitative PCR. Immunohistochemical test was conducted to reveal tumor angiogenesis, tumor proliferation, and apoptosis after the different treatments. Results and Conclusion Compared with RFA or R848 monotherapy, the combination therapy significantly slowed the tumor growth, prolonged the survival time, and shrank the tumor-draining lymph nodes of tumor-bearing mice. The flow cytometry results showed that tumor-infiltrating immune cells, total T cells, the ratio of CD8+ T and NK cells to CD45+ cells, and functional NK cells were obviously increased after the combined treatment. Distal tumor growth was also suppressed, and the profile of tumor-infiltrating immune cells was remodeled, too. In addition, the additive effect of the combination therapy disappeared after NK cell depletion. Furthermore, immunohistochemical results verified that R848 inhibited tumor angiogenesis in murine liver cancer, and the combination therapy promoted tumor cell apoptosis. In conclusion, our data suggest that RFA combined with R848 stimulated a stronger antitumor immune response and effectively inhibited liver cancer progression in a NK cell-dependent manner. Meanwhile, we confirmed that R848 inhibited tumor angiogenesis and promoted apoptosis in murine liver cancer. Overall, this is a promising therapeutic strategy to improve the efficacy of RFA in the treatment of liver cancer and provides a novel option for combined thermal ablation and immunotherapy.